Analisis: Kemampuan Literasi Matematis Ditinjau dari Disposisi Matematis Siswa - Salistia, Salistia; Wida Nadhifah Rahmayati; Nurul Ikhsan Karimah; Jajo Firman Raharjo (CV. AFDIFAL MAJU BERKAH, 2024)
The results of the Mathematical Literacy Research discuss Indonesia's involvement in PISA since 2000, which has never experienced a significant increase in ranking until 2018. Even the 2018 PISA results showed that Indonesia was ranked in the bottom 10 in the world with an average score of Indonesian students mathematical literacy of 359, while the average was 489. This study aims to describe the mathematical literacy skills of grade X students in solving PISA questions in terms of mathematical disposition abilities. This study uses a descriptive type of research with a qualitative approach with three instruments to be used in this study, namely a mathematical disposition scale questionnaire, a mathematical literacy test, and interview guidelines. The research instrument was first consulted with the collaborating lecturer. The results of the disposition test from 33 grade X.1 students were then analyzed to determine the grouping of students' mathematical disposition abilities. The mathematical disposition scale is given to students in three groups: high, medium, and low. The subjects of this study were four students in the class with different levels of mathematical disposition abilities. Based on the results of this study, the literacy abilities of students reviewed in mathematical disposition tend to vary. Students with a high level of disposition have better literacy and problem-solving skills than those with a medium or low level of disposition